Investigations on Germination of Pterocarpus santallnus (Red Sanders) with Special Reference to In-vitro Seed Culture - Anuradha, M.; Pullaiah, T. (Indian Forester, 1998)
Various treatment were tried for efficient pod breakage which is a barrier for seed germination. Effective protocol was standardized for in-vitro germination. High per cent of healthy seedlings were obtained by supplementing the media with 0.1 mg/1 BAP. Multiple shoots were recorded when cultured on media fortified with 3 mg/1 BAP.